2021
DOI: 10.3389/fimmu.2021.745784
|View full text |Cite
|
Sign up to set email alerts
|

MAT2A-Mediated S-Adenosylmethionine Level in CD4+ T Cells Regulates HIV-1 Latent Infection

Abstract: Antiretroviral drugs effectively halt HIV-1 replication and disease progression, however, due to the presence of a stable viral latent reservoir, the infection cannot be cured by antiretroviral drugs alone. Elucidating the molecular mechanisms underlying HIV-1 latent infection remains a critical hurdle that precludes the development of novel therapeutic strategies aiming for a potential functional cure. Cellular metabolism has been reported to affect HIV-1 replication in CD4+ T cells, but it remains largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Corroborating the importance of DNA methylation in HIV-1 latency, Yang et al. found that knocking out methionine adenosyltransferase 2A (MAT2A) in the J-Lat 9.2 cell line led to HIV-1 latency reversal ( Yang et al., 2021 ). MAT2A creates SAM (S-Adenosylmethionine), the methyl donor in histone and DNA methylation, indicating the importance of SAM for maintenance of latency.…”
Section: Metabolic Pathways Affect the Epigenetic Control Of Hiv-1 La...mentioning
confidence: 99%
See 2 more Smart Citations
“…Corroborating the importance of DNA methylation in HIV-1 latency, Yang et al. found that knocking out methionine adenosyltransferase 2A (MAT2A) in the J-Lat 9.2 cell line led to HIV-1 latency reversal ( Yang et al., 2021 ). MAT2A creates SAM (S-Adenosylmethionine), the methyl donor in histone and DNA methylation, indicating the importance of SAM for maintenance of latency.…”
Section: Metabolic Pathways Affect the Epigenetic Control Of Hiv-1 La...mentioning
confidence: 99%
“…Yang et al. further investigated the HIV-1 LTR in the MAT2A knockout and showed decreased CpG island methylation by approximately 50% as well as decreased methylation of histones around the HIV-1 LTR, such as H3K4me3, H3K9me3, and H3K27me3 ( Yang et al., 2021 ). To validate their findings, Yang et al.…”
Section: Metabolic Pathways Affect the Epigenetic Control Of Hiv-1 La...mentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Among the amino acids important for T cells, Met is the sole amino acid responsible for cellular methylome maintenance via the S-adenosyl Met (SAM) pathway, and alterations in the SAM pathway adversely affect T cell function ( 10, 11 ). In complete media, no significant changes were observed in SAM or S-adenosyl homocysteine (SAH) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…conducted a CRISPR knockout screen in an HIV-1 latently infected cell line (J-Lat 9.2) with a human CRISPR metabolic gene knockout library. They found that MAT2A-mediated one-carbon metabolism contributes to regulating HIV latency ( 102 ).…”
Section: Crispr Screening In Immune Cellsmentioning
confidence: 99%